Multidirectional flow pushing and areation of hob pressure boost machine - Wei Hongquan; Li Dongsheng; Guan Pinsan (2016)
The utility model discloses a multidirectional flow pushing and areation of hob pressure boost machine belongs to waste water sewage purifying treatment's technical field. The structure has last load -bearing platform dull and stereotyped (38) top to be equipped with actuating device (9) that high -end fan (39), oxygen boosting drove nitrogen device (43) and oxygen activation, upward dive motor (27) is equipped with to load -bearing platform dull and stereotyped (38) below, the pressure boost pushes away a class device (57). That sheet -metal strip (8) that will be equipped with tombarthite permanent -magnetic clamp (6) are twisted into the oxygen boosting that twist type bent to the luo rotating magnetic field lu of spring form again and are driven the nitrogen device. The pressure boost pushes away helical blade (31) that have the spring to appear on hollow screw axle (17) the lateral wall in a class device (57), and the waist of a lavalle section of thick bamboo (30) is equipped with water magnetization pr